Peran Keteladanan Guru Dalam Pembentukan Nilai Karakter Religius Pada Anak Usia Dini - Febrianingsih Ruhu; Divana Salsabila Khan; Rahmiyanti; Hesti Putri Setianingsih; Besse Nirmala; Zakiyyatul Imamah (Early Childhood Research Journal (ECRJ), 2026)
This literature review looks at fifteen studies from around the world that were published in the past five years. These studies focus on how teachers’ actions influence the development of religious character in young children. The research shows that the way teachers behave during everyday activities, like religious rituals, moral conversations, and social interactions, helps children learn and feel the importance of spiritual and moral values. When teachers model religious behavior, children are more likely to copy prayers, become more independent in their worship, and learn important values like honesty, empathy, patience, and responsibility. When this kind of modeling is included in themed learning activities, it makes learning more interesting, helps children connect emotionally, and improves their understanding of religious values. The review also stresses the need for teachers to be consistent in their behavior, for families to support these values at home, and for schools to have policies that help build religious character. The review also talks about what teachers, school leaders, and researchers can do moving forward.